Vocational Teacher Training – Selection of Teaching Aids - Nagyné Kondor, Rita (International Journal of Engineering and Management Sciences, 2023)
Teacher Training Programmes provide teachers of Vocational Education and Training schools. Students require adequate educational tools they can get in order to improve their learning. They support interaction and give students an impulsive learning environment. This article deals with the prospective vocational teachers, selection and use of teaching aids after their practical pedagogical training in Vocational Education and Training schools.